Circulating Retinol-Binding Protein 4 as a Possible Biomarker of Treatment Response for Ankylosing Spondylitis: An Array-Based Comparative Study - Wu, Jialing; Wu, Xinyu; Chen, Zena; Lv, Qing; Yang, Mingcan; Zheng, Xuqi; Li, Qiuxia; Zhang, Yanli; Wei, Qiujing; Cao, Shuangyan; Li, Xiaomin; Qi, Jun; et al. (Frontiers in Pharmacology, 2020)
Objective: To explore proteins associated with ankylosing spondylitis (AS) and to investigate potential proteins that may predict treatment response of adalimumab (ADA) in AS patients. Methods: In the discovery cohort, 39 AS patients and 20 healthy controls (HCs) were included, and 16 AS patients received ADA treatment for 24 weeks after included. In the validation cohort, 43 AS patients and 39 HCs were enrolled, and all 43 patients received ADA treatment after enrolment. Blood samples and clinical information were collected from two cohorts at baseline from all participants and week 24 from patients received ADA treatment. A Human Antibody Array containing 1,000 proteins was used in the discovery phase, and Elisa kits were used for protein validation. Results: Compared with HCs, we identified 53 differentially expressed proteins (DEPs) in AS patients. Bioinformatics analysis revealed they were mostly enriched in coagulation function-related pathways, acute response signaling and LXR/RXR activation. Bone metabolism pathways were also associated. Comparison between samples of pre- and post-ADA treatment revealed 42 DEPs. They were mostly associated with bone metabolism and inflammation response pathways. Significant enrichment was also found in LXR/RXR activation but not the coagulation function-related pathways. Upstream regulator analysis suggested that most regulators also significantly functioned under usage of ADA. Precisely, seven proteins were abnormally expressed in AS and restored after ADA treatment. Retinol-binding protein 4 (RBP4), one of the seven proteins, was validated that its baseline levels were inversely correlated with improvements in Ankylosing Spondylitis Disease Activity Score- C-reaction protein (ASDAS-CRP). Likewise, percentage changes in RBP4 levels were inversely correlated with changes in ASDAS-CRP score. Conclusions: A dysregulated serum protein profile existed in AS. ADA exerted a considerable but not entire alteration towards the dysregulation. RBP4 could be a biomarker for predicting and monitoring ADA treatment response.